Who Bears the Burden? The Risk of Material Deprivation Among Adults Aged 50 and Older With Varying Caring Roles in Europe - Savela, Roosa-Maria; McKenzie, John (SAGE Publications, 2026)
Europe has experienced multiple crises, including inflation, rising food and living costs, the COVID-19 pandemic, and the 2007–2009 financial crisis, which have contributed to widening social inequalities. These economic pressures may threaten the material well-being of adults aged 50 and older, yet little is known about how they affect those who provide care. This study examined the risk of material deprivation among those with different caring roles in 2021–2022 using the SHARE data. The findings show that co-resident family caregivers, those experiencing financial strain, and individuals with a migrant background are particularly vulnerable to material deprivation. Women carry a disproportionate share of caregiving responsibilities and face higher deprivation risks than men. In contrast, individuals who provide care outside their households or care for grandchildren tend to exhibit better material well-being than those without these roles. Targeted policy measures that both alleviate energy poverty and financial strain are needed.